Pengaruh Literasi Digital Dan Gaya Mengajar Terhadap Kualitas Pembelajaran Siswa Akuntansi Di SMK Swasta Dwi Tunggal Tanjung Morawa - Fadillah Janadiyah; Jufri Darma; La Hanu; Pasca Dwi Putra; Haryani Pratiwi Sitompul (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
This study was conducted to examine the level of influence of digital literacy skills and teaching styles on the quality of learning. The study began with preliminary research through observation, interviews, and the distribution of preliminary questionnaires to students. This study used a quantitative approach with a population of all 166 students in grades X, XI, and XII majoring in Accounting at SMK Swasta Dwi Tunggal Tanjung Morawa in the 2025/2026 academic year. The sample was determined using simple random sampling. Data collection was conducted using a questionnaire designed based on indicators of digital literacy, teaching style, and learning quality. The data was processed using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method supported by the SmartPLS application, which included testing the measurement model through validity and reliability tests, as well as testing the structural model through path coefficient analysis and bootsrapping to test the hypothesis. The test results showed that digital literacy had a significant effect on learning quality with a p-value of 0.000 < 0.05. In addition, teachers' teaching styles were also proven to have a significant effect with a p-value of 0.000 < 0.05. These findings imply that improving digital literacy skills and varied, interactive, and effective teaching styles by teachers can be an important strategy in improving learning quality. Therefore, schools and educators need to optimize the use of digital technology in learning and develop innovative teaching methods to create a more effective learning process and improve student engagement and understanding.